Catalyst for acrylonitrile production
The existing catalyst conversion and selection are solved by using catalytic oxide composite catalysts of elements such as molybdenum, bismuth, cerium, iron, chromium, etc., and oxidizing propylene and isobutylene ammonia to acrylonitrile and methacrylonitrile under high temperature and high pressure conditions, which is a problem of existing catalyst conversion and selection. The problem of insufficient sexuality has achieved efficient catalytic effect.
Patent Information
- Application Number
- CN202380041387.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-21
- Filing Date
- 2023-05-19
- Publication Date
- 2024-12-27
AI Technical Summary
In the process of oxidizing unsaturated hydrocarbon ammonia into corresponding unsaturated nitriles, the conversion and selectivity of existing catalysts are insufficient, especially at high temperatures and pressures, and it is difficult to effectively promote the conversion of propylene and isobutene to acrylonitrile and methacrylate. Nitrile.
The catalytic oxide complex containing molybdenum, bismuth, cerium, iron, chromium and specific proportions of Group A, B and C elements is used as catalysts to react olefins with ammonia and molecular oxygen under high temperature and high pressure conditions through gas phase reaction. Improve the relative ratio of the catalyst to improve catalytic performance.
The total conversion of propylene and isobutene and the selectivity to acrylonitrile are significantly improved, providing better catalytic performance, specifically manifested as high conversion and high selectivity, suitable for ammonia oxidation reactions in fluidized bed reactors.
Smart Images

Figure BDA0005141190280000111 
Figure BDA0005141190280000211 
Figure BDA0005141190280000221
Abstract
Description
Technical Field
[0001] The present invention relates to an improved catalyst composition that can be used for the ammoxidation of unsaturated hydrocarbons to the corresponding unsaturated nitriles. In certain embodiments, the present invention relates to an improved method and catalyst for the ammoxidation of propylene to acrylonitrile and / or the ammoxidation of isobutylene to methacrylonitrile. More specifically, the present invention relates to an improved ammoxidation catalyst comprising a composite of catalytic oxides, the composite comprising molybdenum, bismuth, cerium, iron, chromium, at least one Group A element, at least one Group B element, and optionally at least one Group C element; wherein Group A consists of sodium, potassium, rubidium, and cesium; wherein Group B consists of nickel, cobalt, manganese, zinc, magnesium, calcium, strontium, cadmium, and barium; and wherein Group C consists of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum, and mercury.
[0002] The present invention further relates to an improved process and catalyst for the ammoxidation of propylene to acrylonitrile and / or the ammoxidation of isobutylene to methacrylonitrile using a selective catalyst that can be used to produce unsaturated nitriles in high yields. For example, the catalyst of the present invention exhibits a combination of higher overall propylene conversion and high selectivity to acrylonitrile compared to similar catalysts. Background Art
[0003] Catalysts containing oxides of iron, bismuth and molybdenum promoted with suitable elements are known for the conversion of propylene at elevated temperatures in the presence of ammonia and a source of molecular oxygen (eg, air) (ie, ammoxidation) to produce acrylonitrile.
[0004] There is a continuing need for improved catalysts useful for converting olefins to the corresponding unsaturated nitriles (eg, the ammoxidation of propylene to make acrylonitrile).
[0005] An object of the present invention is a catalyst composition comprising a composite of catalytic oxides, said composite comprising a unique combination of relative ratios of elements providing improved performance in the catalytic ammoxidation of unsaturated hydrocarbons to the corresponding unsaturated nitriles, such as propylene, isobutylene or mixtures thereof, to acrylonitrile, methacrylonitrile and mixtures thereof, respectively.
[0006] Another object of the present invention is to provide a process for the ammoxidation of olefins, comprising reacting olefins with a molecular oxygen-containing gas and ammonia in the gas phase at elevated temperature and pressure in the presence of a catalyst comprising a catalytic oxide composite.
[0007] The present invention also relates to a process for converting an olefin selected from propylene, isobutylene or a mixture thereof into acrylonitrile, methacrylonitrile and a mixture thereof, respectively, by reacting the olefin in the gas phase at elevated temperature and pressure with a gas containing molecular oxygen and ammonia in the presence of a catalyst comprising a composite of the catalytic oxide as described herein. Summary of the invention
[0008] The present invention relates to an improved catalyst and process for the ammoxidation of unsaturated hydrocarbons to the corresponding unsaturated nitriles, for example, propylene and / or isobutylene to acrylonitrile and / or methacrylonitrile, respectively.
[0009] In one embodiment, the catalyst composition comprises a composite of catalytic oxides comprising molybdenum, bismuth, cerium, iron, chromium, at least one Group A element, at least one Group B element, and optionally at least one Group C element, wherein Group A consists of sodium, potassium, rubidium, and cesium; wherein Group B consists of nickel, cobalt, manganese, zinc, magnesium, calcium, strontium, cadmium, and barium; wherein Group C consists of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum, and mercury; and wherein the relative ratios of these elements are represented by formula (1):
[0010] Mo 12 Bi a Ce b Fe c Cr d A e B f C g O x (1)
[0011] in:
[0012] a is about 0.05 to about 4;
[0013] b is about 0.01 to about 3;
[0014] c is about 0.01 to about 4;
[0015] d is from about 0.01 to about 2;
[0016] e is about 0.01 to about 2;
[0017] f is about 0.01 to about 10;
[0018] g is about 0 to about 0.2;
[0019] x is a value determined by the valence requirements of other elements present; and
[0020] wherein c / d is from about 7 to about 12.
[0021] In another embodiment, the catalyst composition comprises a composite of catalytic oxides comprising molybdenum, bismuth, cerium, iron, chromium, at least one Group A element, at least one Group B element, and optionally at least one Group C element, wherein Group A consists of sodium, potassium, rubidium, and cesium; wherein Group B consists of nickel, cobalt, manganese, zinc, magnesium, calcium, strontium, cadmium, and barium; wherein Group C consists of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum, and wherein the relative ratios of these elements are represented by formula (1):
[0022] Mo 12 Bi a Ce b Fe c Cr d A e B f C g O x (1)
[0023] in:
[0024] a is about 0.05 to about 4;
[0025] b is about 0.3 to about 3;
[0026] c is about 0.01 to about 4;
[0027] d is from about 0.01 to about 2;
[0028] e is about 0.01 to about 2;
[0029] f is about 0.01 to about 10;
[0030] g is about 0 to about 0.2;
[0031] x is a value determined by the valence requirements of other elements present; and
[0032] wherein c / d is from about 2 to about 17.
[0033] In some embodiments, the catalyst composition exhibits a scheelite (m-phase + t-phase):β-MMoO4 ratio of not greater than about 0.3, wherein the amounts of m-phase, t-phase, and β-MMoO4 phases are determined using X-ray diffraction and a modified Rietveld analysis model.
[0034] For example, in some embodiments, the catalyst composition comprises a composite of catalytic oxides comprising molybdenum, bismuth, cerium, iron, chromium, at least one Group A element, at least one Group B element, and optionally at least one Group C element, wherein Group A consists of sodium, potassium, rubidium, and cesium; wherein Group B consists of nickel, cobalt, manganese, zinc, magnesium, calcium, strontium, cadmium, and barium; wherein Group C consists of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum, and wherein the relative ratios of these elements are represented by formula (1):
[0035] Mo 12 Bi a Ce b Fe c Cr d A e B f C g O x (1)
[0036] in:
[0037] a is about 0.05 to about 4;
[0038] b is about 0.01 to about 3;
[0039] c is about 0.01 to about 4;
[0040] d is from about 0.01 to about 2;
[0041] e is about 0.01 to about 2;
[0042] f is about 0.01 to about 10;
[0043] g is about 0 to about 0.2;
[0044] x is a value determined by the valence requirements of other elements present; and
[0045] wherein c / d is about 2-36 and the catalyst composition exhibits a scheelite (m-phase + t-phase):β-MMoO4 ratio of not greater than about 0.3, wherein the amounts of m-phase, t-phase and β-MMoO4 phase are determined using X-ray diffraction and a modified Rietveld analysis model.
[0046] Another embodiment is directed to a process for the ammoxidation of olefins. The process comprises reacting olefins with a gas containing molecular oxygen and ammonia in the gas phase at elevated temperature and pressure in the presence of a catalyst comprising a composite of a catalytic oxide comprising molybdenum, bismuth, cerium, iron, chromium, at least one Group A element, at least one Group B element, and optionally at least one Group C element.
[0047] Other objects and features will be in part apparent and in part pointed out hereinafter. DETAILED DESCRIPTION
[0048] The present invention relates to a catalyst composition comprising a composite of catalytic oxides, the composite comprising a unique combination of relative ratios of elements that provide improved performance in the catalytic ammoxidation of unsaturated hydrocarbons to the corresponding unsaturated nitriles, for example, propylene, isobutylene or mixtures thereof, to acrylonitrile, methacrylonitrile and mixtures thereof, respectively.
[0049] The catalyst composition described herein (i.e., except for any optional support) is a composite of catalytic oxides of molybdenum, bismuth, cerium, iron, chromium, at least one Group A element, at least one Group B element, and optionally at least one Group C element. Group A consists of sodium, potassium, rubidium, and cesium. Group B consists of nickel, cobalt, manganese, zinc, magnesium, calcium, strontium, cadmium, and barium. Group C consists of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum, and mercury. In certain embodiments, iron is in excess relative to chromium, and the excess is controlled within certain ranges as described herein.
[0050] In one embodiment, the relative ratios of these elements in the catalyst composition are represented by formula (1):
[0051] Mo 12 Bi a Ce b Fe c Cr d A e B f C g O x (1)
[0052] in:
[0053] a is about 0.05 to about 4;
[0054] b is about 0.01 to about 3;
[0055] c is about 0.01 to about 4;
[0056] d is from about 0.01 to about 2;
[0057] e is about 0.01 to about 2;
[0058] f is about 0.01 to about 10;
[0059] g is about 0 to about 0.2;
[0060] x is a value determined by the valence requirements of other elements present; and
[0061] wherein c / d is from about 2 to about 36.
[0062] In certain embodiments, c / d is about 2 to about 32, about 2 to about 28, about 2 to about 24, about 2 to about 20, about 4 to about 36, about 4 to about 32, about 4 to about 28, about 4 to about 24, about 4 to about 20, about 7 to about 36, about 7 to about 32, about 7 to about 28, about 7 to about 24, about 7 to about 20, about 7 to about 12, about 7 to about 11.5, about 7 to about 11, about 7 to about 10.5, about 7.5 to about 10.5, about 8 to about 10.5, or about 8 to about 10.
[0063] In another embodiment, the catalyst composition has a higher cerium content, and the relative ratios of these elements in the catalyst composition are represented by formula (1):
[0064] Mo 12 Bi a Ce b Fe c Cr d A e B f C g O x (1)
[0065] in:
[0066] a is about 0.05 to about 4;
[0067] b is about 0.3 to about 3;
[0068] c is about 0.01 to about 4;
[0069] d is from about 0.01 to about 2;
[0070] e is about 0.01 to about 2;
[0071] f is about 0.01 to about 10;
[0072] g is about 0 to about 0.2;
[0073] x is a value determined by the valence requirements of other elements present; and
[0074] wherein c / d is from about 2 to about 17.
[0075] In certain embodiments, c / d is about 2 to about 16, about 2 to about 14, about 2 to about 12, about 2 to about 10, about 2 to about 8, or about 2 to about 6.
[0076] In these and other embodiments, a(bismuth) is about 0.05 to about 3.5, about 0.05 to about 3, about 0.05 to about 2.5, about 0.05 to about 2, about 0.05 to about 1.5, about 0.05 to about 1, about 0.1 to about 1, about 0.15 to about 1, about 0.2 to about 1, about 0.25 to about 1, about 0.3 to about 1, about 0.35 to about 1, about 0.4 to about 1, about 0.05 to about 1.25, about 0.05 to about 0.75, about 0.05 to about 0.5, about 0.05 to about 0.4, about 0.05 to about 0.3, about 0.05 to about 0.2, or about 0.05 to about 0.1.
[0077] In these and other embodiments, b(cesium) is about 0.01 to about 2.5, about 0.01 to about 2, about 0.01 to about 1.5, about 0.02 to about 1.5, about 0.04 to about 1.5, about 0.06 to about 1.5, about 0.08 to about 1.5, about 0.1 to about 1.5, about 0.2 to about 1.5, about 0.3 to about 1.5, about 0.4 to about 1.5, or about 0.5 to about 1.5. In certain higher cesium content embodiments, b is about 0.1 to about 3, about 0.2 to about 3, about 0.3 to about 3, about 0.4 to about 3, about 0.5 to about 3, about 0.75 to about 3, about 1 to about 3, about 1.5 to about 3, about 2 to about 3, about 2.5 to about 3, about 0.75 to about 2.5, or about 1 to about 2.5.
[0078] In these and other embodiments, c(iron) is about 0.05 to about 4, about 0.1 to about 4, about 0.15 to about 4, about 0.5 to about 4, about 0.25 to about 4, about 0.3 to about 4, about 0.35 to about 4, about 0.4 to about 4, about 0.45 to about 4, about 0.5 to about 4, about 0.75 to about 4, about 1 to about 4, about 1 to about 3.5, about 1 to about 3, about 0.01 to about 3.5, about 0.01 to about 3, about 0.01 to about 21, about 0.01 to about 1, about 0.01 to about 0.5, about 0.01 to about 0.4, about 0.01 to about 0.3, about 0.01 to about 0.2, about 0.01 to about 0.1, or about 0.01 to about 0.05.
[0079] In these and other embodiments, d(chromium) is about 0.01 to about 1.5, about 0.01 to about 1, about 0.02 to about 1, about 0.04 to about 1, about 0.06 to about 1, about 0.08 to about 1, about 0.1 to about 1, about 0.15 to about 1, about 0.15 to about 0.5, about 0.02 to about 2, about 0.05 to about 2, about 0.1 to about 2, about 0.5 to about 2, about 1 to about 2, or about 1.5 to about 2.
[0080] In these and other embodiments, e(family A) is about 0.01 to about 1.5, about 0.01 to about 1, about 0.01 to about 0.5, about 0.01 to about 0.4, about 0.01 to about 0.3, about 0.01 to about 0.3, about 0.02 to about 0.3, about 0.04 to about 0.3, about 0.06 to about 0.3, about 0.08 to about 0.3, about 0.01 to about 0.3, about 0.02 to about 2, about 0.05 to about 2, about 0.1 to about 2, about 0.5 to about 2, about 1 to about 2, or about 1.5 to about 2.
[0081] In these and other embodiments, f(family B) is about 0.02 to about 10, about 0.04 to about 10, about 0.06 to about 10, about 0.08 to about 10, about 0.1 to about 10, about 0.2 to about 10, about 0.4 to about 10, about 0.6 to about 10, about 0.8 to about 10, about 1 to about 10, about 1.5 to about 10, about 2 to about 10, about 2.5 to about 10, about 3 to about 10, about 3.5 to about 10, about 1 about 4 to about 10, about 4.5 to about 10, about 5 to about 10, about 0.01 to about 8, about 0.01 to about 7, about 0.01 to about 6, about 0.01 to about 5, about 0.01 to about 4, about 0.01 to about 3, about 0.01 to about 2, about 0.01 to about 1, about 0.01 to about 0.5, about 0.01 to about 0.25, about 0.01 to about 0.2, about 0.01 to about 0.1, or about 0.01 to about 0.05.
[0082] In some embodiments, if present, g(family C) is about 0.01 to about 0.2, about 0.02 to about 0.2, about 0.04 to about 0.2, about 0.06 to about 0.2, about 0.08 to about 0.2, or about 0.1 to about 0.2. In an alternative embodiment, g is about 0 to about 0.15, about 0 to about 0.1, about 0 to about 0.05, about 0 to about 0.04, about 0 to about 0.03, about 0 to about 0.02, or about 0 to about 0.01.
[0083] In certain embodiments, A is selected from potassium, rubidium, and cesium. In other embodiments, A is selected from sodium, rubidium, and cesium. In another embodiment, A is selected from sodium, potassium, and cesium. In still another embodiment, A is selected from sodium, potassium, and rubidium. In another embodiment, A is selected from potassium, rubidium, and cesium. In a specific embodiment, A is selected from rubidium and cesium.
[0084] In certain embodiments, B is selected from nickel, manganese, zinc, magnesium, calcium, strontium, cadmium and barium. In another embodiment, B is selected from nickel, cobalt, zinc, magnesium, calcium, strontium, cadmium and barium. In another embodiment, B is selected from nickel, cobalt, manganese, magnesium, calcium, strontium, cadmium and barium. In one embodiment, B is selected from nickel, cobalt, manganese, zinc, calcium, strontium, cadmium and barium. In another embodiment, B is selected from nickel, cobalt, manganese, zinc, magnesium, calcium, strontium, cadmium and barium. In another embodiment, B is selected from nickel, cobalt, manganese, zinc, magnesium, calcium, strontium and barium. In still another embodiment, B is selected from nickel, cobalt, manganese, zinc, magnesium, calcium, strontium and cadmium.
[0085] In certain embodiments, if present, C is selected from gold, ruthenium, rhodium, palladium, osmium, iridium, platinum, and mercury. In another embodiment, C is selected from silver, ruthenium, rhodium, palladium, osmium, iridium, platinum, and mercury. In another embodiment, C is selected from silver, gold, rhodium, palladium, osmium, iridium, platinum, and mercury. In one embodiment, C is selected from silver, gold, ruthenium, palladium, osmium, iridium, platinum, and mercury. In various embodiments, C is selected from silver, gold, ruthenium, rhodium, osmium, iridium, platinum, and mercury. In certain embodiments, C is selected from silver, gold, ruthenium, rhodium, palladium, iridium, platinum, and mercury. In another embodiment, C is selected from silver, gold, ruthenium, rhodium, palladium, osmium, platinum, and mercury. In another embodiment, C is selected from silver, gold, ruthenium, rhodium, palladium, osmium, iridium, and mercury. In another embodiment, C is selected from silver, gold, ruthenium, rhodium, palladium, osmium, iridium, and platinum.
[0086] According to some embodiments, one or more specific elements may be excluded from the catalyst composition (i.e., ingredients including the elements are not added during the preparation of the catalytic oxide component of the catalyst composition). For example, in one embodiment, the catalyst composition does not include potassium. In another embodiment, the catalyst composition does not include rubidium. In another embodiment, the catalyst composition does not include sodium. In another embodiment, the catalyst composition does not include magnesium. In still another embodiment, the catalyst composition does not include calcium. Other elements or promoters may be included in the catalyst composition. For example, in some embodiments, the catalyst composition includes one or more elements selected from phosphorus, tin, indium, antimony, tellurium, lithium, thallium, boron, germanium and rare earth elements (defined herein as any one of La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm or Yb). For example, in one embodiment, the catalyst composition contains a small amount of phosphorus, which has a beneficial effect on the wear resistance of the catalyst.
[0087] Bismuth, cerium, iron, and chromium can be introduced into the catalyst composition in the form of any compound containing the element, such as an oxide or as a salt that will produce an oxide after calcination. In certain embodiments, water-soluble salts that can be easily dispersed in the catalyst but form stable oxides after heat treatment can be used. For example, in one embodiment, sources for introducing these elements include bismuth nitrate, cerium nitrate, iron nitrate, and chromium nitrate.
[0088] The molybdenum component of the catalyst composition may be introduced from any molybdenum oxide. However, it is preferred to utilize a hydrolyzable or decomposable molybdenum salt as the source of molybdenum (eg, ammonium heptamolybdate).
[0089] Other required or optional components (i.e., elements of Groups A, B, and C) and optional elements or promoters of the catalyst composition (e.g., P, Sn, Te, B, Ge, In, or mixtures thereof) may be derived from any suitable source. For example, cobalt, nickel, and magnesium may be introduced into the catalyst using nitrates. Additionally, magnesium may be introduced into the catalyst as an insoluble carbonate or hydroxide, which produces an oxide upon heat treatment. Phosphorus may be introduced into the catalyst as an alkali metal salt, an alkaline earth metal salt, an ammonium salt, or phosphoric acid.
[0090] The required and / or optional base components (e.g., Rb, Li, Na, K, Cs, or mixtures thereof) in the catalyst composition can be introduced into the catalyst as oxides or as salts which will produce oxides after calcination. In certain embodiments, such elements are incorporated into the catalyst using readily available and soluble salts (e.g., nitrates).
[0091] For the conversion of propylene, ammonia and oxygen to acrylonitrile, it has been determined that comprising certain elements is not conducive to obtaining a catalyst with improved acrylonitrile yield. For example, the catalyst composition comprising vanadium production is more active in the reaction of the propylene feedstock and has a lower selectivity to the desired product, thereby producing more carbon oxides (COx) and less acrylonitrile. Therefore, in one embodiment, the catalyst composition is substantially free of vanadium. As used herein, "substantially free of" means, relative to vanadium, less than 0.2:12 in terms of the atomic ratio of molybdenum.
[0092] The catalyst compositions described herein can be analyzed using X-ray diffraction techniques, such as those described below in Example 3. In certain embodiments, the catalyst compositions described herein exhibit certain X-ray diffraction (XRD) patterns including peaks at 2θ angles of about 23±0.3 degrees, about 28±0.3 degrees, and / or about 26.5±0.3 degrees.
[0093] In one embodiment, the catalyst composition exhibits X-ray diffraction peaks at 2θ angles of about 28±0.3 degrees and about 26.5±0.3 degrees, and the intensity ratio of the strongest X-ray diffraction peak within the 2θ angle of about 28±0.3 degrees to the strongest X-ray diffraction peak within the 2θ angle of about 26.5±0.3 degrees is about 0.50 or less, about 0.40 or less, about 0.30 or less, about 0.20 or less, about 0.18 or less, about 0.16 or less, about 0.14 or less, about 0.12 or less, or about 0.1 or less. For example, about 0.05 to about 0.5, 0.05 to about 0.4, about 0.1 to about 0.4, about 0.1 to about 0.3, or about 0.1 to about 0.2.
[0094] In certain embodiments, the catalyst composition exhibits X-ray diffraction peaks at 2θ angles of about 23±0.3 degrees and about 26.5±0.3 degrees, and the ratio of the intensity of the most intense X-ray diffraction peak within the 2θ angle of about 23±0.3 degrees to the most intense X-ray diffraction peak within the 2θ angle of about 26.5±0.3 degrees is about 0.1 or greater, about 0.11 or greater, about 0.12 or greater, about 0.13 or greater, about 0.14 or greater, about 0.15 or greater, about 0.16 or greater, about 0.17 or greater, about 0.18 or greater, about 0.19 or greater, about 0.20 or greater, about 0.25 or greater, about 0.3 or greater, about 0.35 or greater, about 0.4 or greater, about 0.45 or greater, or about 0.5 or greater. For example, about 0.1 to about 0.5, about 0.11 to about 0.5, about 0.12 to about 0.5, about 0.13 to about 0.5, about 0.14 to about 0.5, about 0.15 to about 0.5, about 0.15 to about 0.5, about 0.15 to about 0.4, about 0.15 to about 0.3, or about 0.15 to about 0.2.
[0095] In certain embodiments, the catalyst composition exhibits X-ray diffraction peaks at 2θ angles of about 23±0.3 degrees and about 28±0.3 degrees, and the ratio of the intensity of the most intense X-ray diffraction peak within the 2θ angle of about 23±0.3 degrees to the most intense X-ray diffraction peak within the 2θ angle of about 28±0.3 degrees is about 0.5 or greater, about 0.6 or greater, about 0.7 or greater, about 0.8 or greater, about 0.9 or greater, about 1 or greater, about 1.2 or greater, about 1.4 or greater, about 1.6 or greater, about 1.8 or greater, about 2 or greater, about 2.2 or greater, about 2.4 or greater, about 2.6 or greater, about 2.8 or greater, or about 3 or greater. For example, about 0.2 to about 3, about 0.2 to about 2, about 0.3 to about 3, or about 0.3 to about 2. In another embodiment, the catalyst composition exhibits X-ray diffraction peaks at 2θ angles of about 23±0.3 degrees and about 28±0.3 degrees, and the intensity ratio of the strongest X-ray diffraction peak within the 2θ angle of about 23±0.3 degrees to the strongest X-ray diffraction peak within the 2θ angle of about 28±0.3 degrees is about 0.5 to about 2, about 1 to about 2, about 1.2 to about 2, about 1.4 to about 2, or about 1.4 to about 1.8.
[0096] In certain other embodiments, the catalyst composition can be analyzed using X-ray diffraction (XRD) and modified Rietveld analysis. In this regard, the crystallographic phases of the catalytic composition are analyzed using XRD analysis known in the art. The diffraction pattern of the catalytic composition is then analyzed using the modified Rietveld analysis described herein.
[0097] According to the modified Rietveld analysis, the complete diffraction pattern is simulated by ab initio calculation based on the atomic structure of the individual phases in the hypothetical phase composition of the measured sample. The correspondence between the simulated and measured diffraction patterns can then be achieved by determining the covariance.
[0098] Rietveld analysis can be performed using GSAS software as described in Larson et al., "General Structural Analysis System (GSAS)", Los Alamos National Laboratory Report LAUR 86-784 (2004) and Toby, "EXPGUI, A Graphical User Interface for GSAS", J. Appl. Cryst., 34, 210-221 (2001), both of which are incorporated herein by reference. GSAS and EXPGUI are available at
[0099] Obtained from https: / / subversion.xor.aps.anl.gov / trac / EXPGUI / wiki.
[0100] The modified Rietveld model consists of four stages which can be described as follows.
[0101]
[0102] As used herein, "m-phase" refers to a monoclinic scheelite-like composition as determined by modified Rietveld analysis as described herein.
[0103] As used herein, "t-phase" refers to a tetragonal scheelite-like composition as determined by modified Rietveld analysis as described herein.
[0104] The starting atomic coordinates are the same as reported in the reference. The starting lattice parameters are given here and differ slightly from the literature values. The thermal displacement parameter U iso by Given as units.
[0105] β-FeMoO4, structure described in Sleight et al., Inorg. Chem. 7, 1093-8 (1968), which is incorporated herein by reference.
[0106] Space group C2 / m, β=107.08°.
[0107] Fe U iso is 0.01, Mo is 0.005, and O is 0.02.
[0108] The initial Fe occupancies were both 1.000.
[0109] Fe2(MoO4)3, structure described in Chen, Mater. Res. Bull., 14, 1583-90 (1979), which is incorporated herein by reference.
[0110] Space group P21 / a, β=125.60°.
[0111] U of Fe and Mo iso is 0.01, and O is 0.02.
[0112] Ce2(MoO4)3, structure described in Brixner et al., J. Solid State Chem., 5, 247-9 (1972), which is incorporated herein by reference.
[0113] Space group C2 / c, β=108.73°.
[0114] Ce and Mo's U iso is 0.01, and O is 0.02.
[0115] The initial Ce occupancy is 1.000.
[0116] NaBi(MoO4)2, structure described in Waskowska et al., Solid State Chem., 178, 2218-24 (2005), which is incorporated herein by reference.
[0117] Space group I41 / a,
[0118] Mo's U iso It is 0.01, and those of Na, Bi and O are 0.02.
[0119] The background is modeled using either a 3-term cosine Fourier series or a 3-term shifted Chebyshev polynomial.
[0120] The amorphous component of the catalyst was modeled using seven Debye scattering terms corrected for thermal motion (diffuse scattering function 1 in GSAS). Each term was modeled as a thermal shift parameter (U) of The Si-O distances of the seven items are fixed at 1.55, 2.01, 2.53, 2.75, 3.49, 4.23 and And its amplitude is optimized in the Rietveld fit.
[0121] Phases and parameters were gradually introduced into the model to ensure stable refinement. At each step, 5-10 cycles of least squares refinement were performed to allow the model to stabilize before the next component was introduced. A damping factor of 5 (i.e., 50%) for all parameters (except the conversion factor of the phase) was used to reduce overshoot and oscillation. The procedure was as follows:
[0122] 1. The starting model contains only the β-FeMoO4 phase, and its lattice parameters are fixed and its profile Y (Lorentzian lattice strain) is set to 75. Only 3 background functions and the conversion factor of the β-FeMoO4 phase are changed.
[0123] 2. Add shift parameter (sample displacement).
[0124] 3. Allowing the lattice parameters of β-FeMoO4 to vary.
[0125] 4. Three other phases were added, all with fixed lattice parameters and profile X (Lorentzian Scherrer broadening) set to 20, and their scaling factors were allowed to vary.
[0126] 5. Add 7 diffuse scattering terms and allow their amplitudes to vary.
[0127] 6. Allowing the lattice parameters of the two scheelite-like phases to vary.
[0128] 7. The profile Y of β-FeMoO4 and the profiles X of the other three phases are allowed to vary.
[0129] 8. Allow the Fe occupancy of the β-FeMoO4 phase and the Ce occupancy of the Ce2(MoO4)3 phase to vary.
[0130] 9. Continue least squares refinement until convergence, that is, (displacement / esd) of all parameters 2 The sum is less than 0.01.
[0131] The XRD peaks associated with β-MMoO4 phase (M = Ni, Mg, Fe), Fe2(MoO4)3 phase, m phase, and t phase are refined as described herein, and the ratio of scheelite (m phase + t phase): β-MMoO4 is calculated based on the refined values. In certain embodiments, the catalyst composition of the present invention exhibits a significantly reduced scheelite: β-MMoO4 ratio. For example, the scheelite: β-MMoO4 ratio calculated after Rietveld refinement is not greater than about 0.3, not greater than about 0.25, not greater than about 0.2, not greater than about 0.15, not greater than about 0.1, not greater than about 0.09, not greater than about 0.08, not greater than about 0.07, not greater than about 0.06, not greater than about 0.05, not greater than about 0.04, not greater than about 0.03, not greater than about 0.02, or not greater than about 0.01. Catalysts exhibiting a significant reduction in the scheelite:β-MMoO4 ratio after Rietveld refinement in combination with the compositional requirements (including the c (iron) to d (chromium) atomic ratios disclosed above) provide high conversions and desirable selectivities in the ammoxidation of olefins, such as propylene to produce acrylonitrile.
[0132] The catalyst composition comprising oxides of molybdenum, bismuth, cerium, iron, chromium, at least one A group element, at least one B group element and optionally at least one C group element as described herein can be supported or unsupported (i.e., the catalyst composition can further include a carrier). Suitable carriers can be selected, for example, from silicon dioxide, aluminum oxide, zirconium, titanium dioxide or mixtures thereof. Carriers are generally used as binders for catalysts to produce harder and more wear-resistant catalysts, and therefore when ammoxidation is carried out in a fluidized bed reactor, supported catalysts are generally used. For commercial applications, appropriate blends of the catalytic oxide and carrier described above are selected to obtain acceptable activity and hardness (wear resistance) of the catalyst. The increase in the catalytic oxide ratio will increase the activity of the catalyst, but reduce the hardness of the catalyst. Generally, when employed, the support comprises about 30 wt.% to about 70 wt.%, about 35 wt.% to about 70 wt.%, about 40 wt.% to about 70 wt.%, about 40 wt.% to about 65 wt.%, about 40 wt.% to about 60 wt.%, about 40 wt.% to about 55 wt.%, or about 45 wt.% to about 55 wt.% of the catalyst composition. In certain embodiments, the support material may contain one or more promoter elements (e.g., silica sol containing sodium (Na)), and such promoter elements may be incorporated into the catalyst composition via the support material.
[0133] In one embodiment, the catalyst is loaded with silica sol. If the average colloidal particle diameter of the silica sol is too small, the surface area of the catalyst produced will increase, and the catalyst will show a reduced selectivity. If the colloidal particle diameter is too large, the anti-wear strength of the catalyst produced will be poor. Therefore, in certain embodiments, the average colloidal particle diameter of the silica sol is between about 8nm and about 50nm.
[0134] The catalyst of the present invention can be prepared by any of the numerous catalyst preparation methods known to those skilled in the art. For example, the catalyst can be manufactured by coprecipitating various components. The coprecipitated material can then be dried and ground to an appropriate size. Alternatively, the coprecipitated material can be slurried and spray dried according to conventional techniques. The catalyst can be extruded into particles or formed into spears in oil, as is well known in the art. Regarding the specific procedures for manufacturing the catalyst, see U.S. Patents Nos. 5,093,299, 4,863,891 and 4,766,232, which are incorporated herein by reference. In one embodiment, the catalyst components can be mixed with the carrier in the form of a slurry and then dried. In another embodiment, the catalyst components can be impregnated on silica or other carriers.
[0135] The catalyst composition is prepared by mixing the compounds of the desired elements in appropriate molar amounts to obtain the desired catalytic oxide composition. Generally, for silica-supported catalysts, an aqueous solution of ammonium heptamolybdate is mixed with a silica sol to which a slurry containing other element compounds (e.g., nitrates) is added. The solid material is then dried, denitrified, and calcined. The catalyst may be spray dried at a temperature of about 110°C to about 350°C, about 110°C to about 250°C, or about 110°C to about 180°C. The denitrification temperature may be in the range of about 100°C to 500°C or about 250°C to 450°C. Calcination may be carried out at a temperature between about 300°C to about 700°C or between about 350°C to about 650°C. The composition of the resulting catalytic oxide may be determined by methods known in the art such as inductively coupled plasma (ICP) analysis.
[0136] The catalyst described herein can be used in an ammoxidation process for converting unsaturated hydrocarbons into corresponding unsaturated nitriles by reacting olefins with a gas containing molecular oxygen and ammonia in the presence of a catalyst in a gas phase at elevated temperature and pressure. For example, olefins selected from propylene, isobutylene or mixtures thereof are converted into acrylonitrile, methacrylonitrile and mixtures thereof, respectively, by reacting olefins with a gas containing molecular oxygen and ammonia in the presence of a catalyst in a gas phase at elevated temperature and pressure.
[0137] In certain embodiments, the ammoxidation reaction is carried out in a fluidized bed reactor. For example, the reactor design described in U.S. Patent No. 3,230,246 is suitable, which is incorporated herein by reference. In another embodiment, other types of known reactors, such as transport line reactors, can be used for the ammoxidation reaction.
[0138] Conditions for the ammoxidation reaction are described, for example, in U.S. Pat. Nos. 5,093,299, 4,863,891, 4,767,878, and 4,503,001, which are incorporated herein by reference. Generally, the ammoxidation process is carried out by contacting propylene or isobutylene with a fluidized bed catalyst at elevated temperatures in the presence of ammonia and oxygen to produce acrylonitrile or methacrylonitrile.
[0139] Any suitable source of oxygen may be used. However, for economic reasons, it may be desirable to utilize air as a source of oxygen. In certain embodiments, the molar ratio of oxygen to olefin in the feed is from about 0.5:1 to about 4:1 or from about 1:1 to about 3:1. In certain specific embodiments, the olefin comprises propylene, the source of oxygen comprises air, and the molar ratio of air to propylene is from about 5:1 to about 20:1, from about 5:1 to about 15:1, from about 6:1 to about 12:1, from about 7:1 to about 15:1, from about 8:1 to about 15:1, from about 8:1 to about 14:1, from about 8:1 to about 13:1, or from about 8:1 to about 12:1.
[0140] Typically, for economic reasons, the molar ratio of ammonia to olefin in the reaction feed is about 2: 1 or less. For example, in certain embodiments, the molar ratio of ammonia to olefin in the reaction feed may vary between 0.5: 1-2: 1. For example, in one embodiment, the molar ratio of ammonia to olefin in the reaction feed is about 0.5: 1-about 2: 1, about 0.5: 1-about 1.5: 1, about 0.5: 1-about 1.4: 1, about 0.5: 1-about 1.3: 1, about 0.5: 1-about 1.2: 1, about 0.5: 1-about 1.1: 1, about 0.5: 1-about 1: 1, or about 0.75: 1-about 1: 1.
[0141] It has been found that in certain embodiments, the catalysts described herein provide acrylonitrile in high yield with a relatively low ammonia to propylene feed ratio. For example, in one embodiment, the olefin comprises propylene and the molar ratio of ammonia to propylene is about 0.9: 1-about 1.3: 1, about 0.9: 1-about 1.2: 1, about 0.9: 1-about 1.1: 1, about 1: 1-about 1.1: 1, or about 1: 1-about 1.05: 1. These "low ammonia conditions" help reduce unreacted ammonia in the reactor effluent, which is called "ammonia breakthrough", which helps to reduce process waste. Specifically, before recovering acrylonitrile, unreacted ammonia must be removed from the reactor effluent. Unreacted ammonia is generally removed by contacting the reactor effluent with sulfuric acid to produce ammonium acrylate, which in both cases results in a process waste stream to be treated and / or disposed of. Further, since ammonia is a relatively expensive reagent, the increasingly effective use of ammonia further reduces production costs.
[0142] In one embodiment for producing acrylonitrile from propylene, the ratio of ammonia to propylene is from about 0.9:1 to about 1.3:1 and the ratio of air to propylene is from about 8.0:1 to about 12.0:1.
[0143] The reaction can be carried out at a temperature of about 260°C to about 600°C, about 310°C to 500°C, or about 350°C to about 480°C. The contact time, while not critical, is generally about 0.1 to about 50 seconds. In certain embodiments, the contact time is about 1 to about 15 seconds.
[0144] The products of the reaction may be recovered and purified by any known method. One such method includes washing the effluent gas from the reactor with cold water or a suitable solvent to remove the reaction products, and then purifying the reaction products by distillation.
[0145] It has been found that the catalysts of the present invention surprisingly contribute to improved olefin conversion. For example, by utilizing the catalysts of the present invention in an olefin ammoxidation process in which the olefin comprises propylene, the olefin conversion is about 85% or greater, about 86% or greater, about 87% or greater, about 88% or greater, about 89% or greater, about 90% or greater, about 91% or greater, about 92% or greater, about 93% or greater, about 94% or greater, about 95% or greater, about 96% or greater, about 97% or greater, about 98% or greater, about 99% or greater, about 99.1% or greater, about 99.2% or greater, about 99.3% or greater, about 99.7% or greater, about 99.8% or greater, about 99.6% or greater, about 99.7% or greater, about 99.8% or greater, or about 99.9% or greater and generally about 98% to about 99%.
[0146] In some embodiments, it has been found that the catalyst of the present invention unexpectedly helps to increase the nitrile yield. For example, by utilizing the catalyst of the present invention in an olefin ammoxidation process in which the olefin comprises propylene, the nitrile yield is about 70% or greater, about 72% or greater, about 74% or greater, about 76% or greater, about 78% or greater, about 80% or greater, about 82% or greater, about 84% or greater, about 86% or greater, about 88% or greater, or about 90% or greater.
[0147] Although the catalyst is described herein for the ammoxidation of propylene to acrylonitrile, the catalyst can also be used to oxidize propylene to acrylic acid. Such a process is generally a two-stage process, wherein propylene is converted primarily to acrolein in the presence of a catalyst in a first stage and acrolein is converted primarily to acrylic acid in the presence of a catalyst in a second stage. The catalyst described herein is suitable for the first stage of the oxidation of propylene to acrolein.
[0148] Example
[0149] To illustrate the invention, catalysts of the invention and similar catalysts omitting one or more of the required elements and / or containing the elements in different proportions were prepared and then evaluated under similar reaction conditions. These examples are provided for illustrative purposes only.
[0150] Example 1 - Catalyst Preparation
[0151] Sample 1. Prepare the formula 50% as follows
[0152] Ni 3.85 Mg 2.89 Fe 0.843 R 0.13 Cr 0.082 Bi 1.35 Ce 0.67 Mo 12 O 47.57 +50wt%SiO2 catalyst
[0153] The metal nitrate Fe(NO3) is added in the following order: 3.9H2O (32.15 g), Ni(NO3)2.6H2O (105.83 g), Mg(NO3)2.6H2O (69.98 g), Bi(NO3)3.5H2O (61.77 g), Cr(NO3)3.9H2O (3.08 g), RbNO3 (1.81 g), (NH4)2Ce(NO3)6 (69.81 g of 50% solution) were dissolved in water (30.51 g) at about 55°C to form a mixed metal nitrate solution. Ammonium heptamolybdate (AHM) (200.07 g) was dissolved in 220.08 g of distilled water at about 65°C. Silica (746.27 of 33.5% SiO2 sol) was then added, followed by the mixed metal nitrate solution. The resulting slurry was then spray dried. The obtained material was denitrified at 290°C for 3 hours and at 425°C for 3 hours, and then calcined at 580°C in air for 3 hours.
[0154] Sample 2. Prepare 50%
[0155] Ni 3.43 Mg 2.57 Fe 1.50 R 0.13 Cr 0.36 Bi 0.60 Ce 1.20 Mo 12 O 48.16 +50 wt% SiO2 catalyst. Metal nitrates Fe(NO3)3.9H2O (58.43 g), Ni(NO3)2.6H2O (96.15 g), Mg(NO3)2.6H2O (63.56 g), Bi(NO3)3.5H2O (28.05 g), Cr(NO3)3.9H2O (13.99 g), RbNO3 (1.85 g), (NH4)2Ce(NO3)6 (126.91 g of 50% solution) were dissolved in water (29.11 g) at about 55°C in the following order to form a mixed metal nitrate solution. Ammonium heptamolybdate (AHM) (204.29 g) was dissolved in 224.72 g of distilled water at about 65°C. Silica (746.27 of 33.5% SiO2 sol) was then added, followed by the mixed metal nitrate solution. The resulting slurry was then spray dried.The obtained material was denitrified at 290°C for 3 hours and at 425°C for 3 hours and then calcined at 580°C in air for 3 hours.
[0156] Sample 3. Prepare 50%
[0157] Ni 3.89 Mg 2.92 Fe 1.75 R0.19 Cr 0.05 Bi 0.19 Ce 1.22 Mo 12 O 48.32 +50 wt% SiO2 catalyst. Metal nitrates Fe(NO3)3.9H2O (69.29 g), Ni(NO3)2.6H2O (110.82 g), Mg(NO3)2.6H2O (73.29 g), Bi(NO3)3.5H2O (9.24 g), Cr(NO3)3.9H2O (1.91 g), RbNO3 (2.7 g), (NH4)2Ce(NO3)6 (132.88 g of 50% solution) were dissolved in water (29.69 g) at about 55°C to form a mixed metal nitrate solution. Ammonium heptamolybdate (AHM) (207.69 g) was dissolved in 228.45 g of distilled water at about 65°C. Silica (746.27 of 33.5% SiO2 sol) was then added, followed by the mixed metal nitrate solution. The resulting slurry was then spray dried.The obtained material was denitrified at 290°C for 3 hours and at 425°C for 3 hours and then calcined at 580°C in air for 3 hours.
[0158] Sample 4. Prepare the formula 50% as follows
[0159] Ni 3.89 Mg 2.92 Fe 0.36 R 0.19 Cr 0.05 Bi 0.36 Ce 2.43 Mo 12 O 48.92 +50wt% SiO2 catalyst. Metal nitrates Fe(NO3)3·9H2O (13.69 g), Ni(NO3)2·6H2O (105.13 g), Mg(NO3)2·6H2O (69.52 g), Bi(NO3)3·5H2O (16.44 g), Cr(NO3)3·9H2O (1.81 g), RbNO3 (2.56 g), (NH4)2Ce(NO3)6 (252.09 g of 50% solution) were dissolved in water (23.24 g) at about 55°C in the following order to form a mixed metal nitrate solution. Ammonium heptamolybdate (AHM) (197.01 g) was dissolved in 216.72 g of distilled water at about 65°C. Silica (746.27 of 33.5% SiO2 sol) was then added, followed by the mixed metal nitrate solution. The resulting slurry was then spray dried.The obtained material was denitrified at 290°C for 3 hours and at 425°C for 3 hours and then calcined at 580°C in air for 3 hours.
[0160] Comparative Catalysts
[0161] Comparative Example A. 50 wt % of the formula
[0162] Ni 1.81 Mg 1.36 Fe 2.64 R 0.13 Cr 0.13 Bi 1.05 Ce 2.11 Mo 12 O 49.18 +50wt% SiO2 catalyst. Metal nitrates Fe(NO3)3·9H2O (96.57 g), Ni(NO3)2·6H2O (47.67 g), Mg(NO3)2·6H2O (31.53 g), Bi(NO3)3·5H2O (46.36 g), Cr(NO3)3·9H2O (4.63 g), RbNO3 (1.74 g), (NH4)2Ce(NO3)6 (209.69 g of 50% solution) were dissolved in water (25.39 g) at about 55°C in the following order to form a mixed metal nitrate solution. Ammonium heptamolybdate (AHM) (192.03 g) was dissolved in 211.23 g of distilled water at about 65°C. Silica (746.27 of 33.5% SiO2 sol) was then added, followed by the mixed metal nitrate solution. The resulting slurry was then spray dried.The obtained material was denitrified at 290°C for 3 hours and at 425°C for 3 hours and then calcined at 580°C in air for 3 hours.
[0163] Several other comparative catalysts were prepared using the techniques and procedures described in Example 1 of U.S. Patent No. 7,071,140. In the catalysts of Comparative Examples BE, one or more of chromium, cerium or rubidium was omitted from the preparation. In Comparative Examples D and E, cesium (CsNO3) and potassium (KNO3) were substituted for rubidium, respectively.
[0164] Comparative Example B. 50 wt% Ni 5.0 Mg 2.0 Fe 1.8 Bi 0.45 Ce 0.9 R 0.15 Mo 12 O 48.25 +50wt%SiO2.
[0165] Comparative Example C. 50wt% Ni 5.0 Mg 2.0 Fe 1.8 Bi0.45 Cr 0.1 R 0.15 Mo 12 O 46.6 +50wt%SiO2.
[0166] Comparative Example D. 50 wt%
[0167] Ni 5.0 Mg 2.0 Fe 1.8 Bi 0.45 Ce 0.9 Cr 0.1 K 0.15 Mo 12 O 48.4 +50wt%SiO2.
[0168] Comparative Example E. 50 wt%
[0169] Ni 5.0 Mg 2.0 Fe 1.8 Bi 0.45 Ce 0.9 Cr 0.1 Cs 0.15 Mo 12 O 48.4 +50wt%SiO2.
[0170] Comparative Example F. 50 wt%
[0171] Ni 5.0 Mg 2.0 Fe 1.8 Bi 0.45 Ce 0.9 Cr 0.1 R 0.15 Mn 1.0 Mo 12 O 49.4 + 50 wt% SiO2. The Catalyst To the catalyst preparation was added manganese Mn(NO3)2 (32.699 g of a 51.1% solution).
[0172] Comparative Example G.50 wt%
[0173] Ni 5.0 Mg 2.0 Fe 1.8 Bi 0.45 Ce 0.9 Cr 0.1 R 0.15 Pd 0.1 Mo 12 O 48.5+50 wt% SiO2. The Catalyst To the catalyst preparation was added the noble metal palladium Pd(NO3)2 (2.2 g).
[0174] Comparative Example H. 50 wt%
[0175] Ni 5.0 Mg 2.0 Fe 1.8 Bi 0.45 Ce 0.9 Cr 0.1 R 0.15 V 0.5 Mo 12 O 49.65 +50 wt% SiO2. The Catalyst Vanadium NH4VO3 (5.514 g) was added to the catalyst preparation.
[0176] Comparative Example I. 50 wt%
[0177] Ni 5.0 Mg 2.0 Fe 1.8 Bi 0.45 Ce 0.15 Cr 0.3 R 0.15 Mo 12 O 47.2 +50wt% SiO2. The catalyst was prepared in which the moles of cerium plus the moles of chromium equaled the moles of bismuth on an atomic basis. The catalyst formulation was as follows: Fe(NO3)3.9H2O (72.939 g), Ni(NO3)2.6H2O (145.83 g), Mg(NO3)2.6H2O (51.434 g), Bi(NO3)3.5H2O (21.894 g), RbNO3 (2.219 g) and (NH4)2Ce(NO3)6 (16.496 g of 50% solution) were dissolved in water at about 70°C in a 1000 ml beaker. Ammonium heptamolybdate (AHM) (212.504 g) was dissolved in 310 ml of distilled water. To this solution was added CrO3 (3.009 g) dissolved in 20 ml of water. Silica (871.08 g of 28.75% SiO2 sol) was then added, followed by the metal nitrates.
[0178] Comparative Example J. 50 wt%
[0179] Ni 5.0 Mg 2.0 Fe 1.8 Bi 0.45 Ce 0.1 Cr 0.1 R 0.15 Mo 12O 46.8 +50wt% SiO2. The catalyst was prepared in which the amount of cerium plus the amount of chromium was less than the amount of bismuth on an atomic basis. The catalyst formulation was as follows: Fe(NO3)3.9H2O (73.642 g), Ni(NO3)2.6H2O (147.236 g), Mg(NO3)2.6H2O (51.93 g), Bi(NO3)3.5H2O (22.105 g), RbNO3 (2.24 g), (NH4)2Ce(NO3)6 (11.104 g of 50% solution) were dissolved in water at 70°C in a 1000 ml beaker. Ammonium heptamolybdate (AHM) (214.553 g) was dissolved in 310 ml of distilled water. To this solution was added CrO3 (1.013 g) dissolved in 20 ml of water. Silica (871.08 g of 28.75% SiO2 sol) was then added, followed by the metal nitrates.
[0180] Comparative Example K. 50 wt%
[0181] Ni 5.0 Mg 2.0 Fe 1.8 Bi 2.0 Ce 0.9 Cr 0.1 R 0.15 Mo 12 O 46.8 +50wt% SiO2. The catalyst is prepared in which the amount of cerium plus the amount of chromium is less than the amount of bismuth on an atomic basis. The catalyst formulation is as follows: Fe(NO3)3.9H2O (61.264 g), Ni(NO3)2.6H2O (122.488 g), Mg(NO3)2.6H2O (43.201 g), Bi(NO3)3.5H2O (81.732 g), RbNO3 (1.863 g), (NH)2Ce(NO3)6 (83.136 g of 50% solution) are dissolved in a 1000 ml beaker.
[0182] 70°C water. Ammonium heptamolybdate (AHM) (178.49 g) was dissolved in 310 ml of distilled water. To this solution was added CrO3 (0.843 g) dissolved in 20 ml of water. Then silica (871.08 g of 28.75% SiO2 sol) was added, followed by the metal nitrates.
[0183] ICP analysis was performed on the resulting material and confirmed that the catalyst comprised the molecular formula set forth above.
[0184] Example 2 - Catalyst Testing
[0185] Catalyst samples 1-4 and comparative catalysts were tested in a 40cc fluidized bed reactor. Propylene was fed into the reactor at a rate of 0.06 WWH (i.e., propylene weight / catalyst weight / hour). The pressure in the reactor was maintained at 10 psig. The reaction temperature was 430°C. After a stabilization period of ~20 hours, samples of the reaction products were collected. The reactor effluent was collected in a bubble scrubber containing a cold HCl solution. The exhaust gas rate was measured with a soap film meter, and the exhaust gas composition was determined at the end of the run by means of a gas chromatograph equipped with a column gas analyzer. At the end of the recovery run, the entire scrubber liquid was diluted to about 200 gms with distilled water. The weighed amount of 2-butanone was used as an internal standard in a ~50 g aliquot dilute solution. A 2 μl sample was analyzed in a GC equipped with a flame ionization detector and a Carbowax column. The amount of NH3 was determined by titrating the free HCl excess with a NaOH solution. The results are shown below.
[0186] Table 1
[0187]
[0188]
[0189] Notes:
[0190] 1. The test catalyst composition contained 50% catalyst oxide and 50% SiO2 by weight.
[0191] 2. "Total C3 Conv." is the mole percent of propylene converted to all products in a single pass.
[0192] 3. “Conv. To AN” is the mole percentage of propylene converted to acrylonitrile in a single pass.
[0193] 4. "Sel. to AN" is the ratio of moles of acrylonitrile produced to moles of propylene converted, expressed as a percentage.
[0194] Example 3 - X-ray diffraction analysis
[0195] Fresh catalyst samples were analyzed as received without grinding. Sample powder was added to a zero background cell to make a flat and densely packed sample for XRD analysis. Typical conditions used for a Panalytical Empyrean Series 3 diffractometer are as follows:
[0196] Sample rotation
[0197] Cu Kα radiation (wavelength Kα1 )
[0198] X-ray generator 45KV, 40mA
[0199] Incident beam optics:
[0200] Divergence slit: fixed slit 1 / 8°
[0201] Anti-scatter slit: fixed slit 1 / 2°
[0202] Diffractive Beam Optics:
[0203] Soller slit: Soller slit 0.02rad
[0204] Anti-scatter slit: AS slit 7.5mm
[0205] Scanning range 5°-100°
[0206] Step length 0.013°
[0207] Total scanning time 4:00 (240 minutes)
[0208] The X-ray diffraction peaks of Catalyst Sample 2 and Comparative Example A were also evaluated and further refined using Rietveld refinement as described in detail herein. The results are reported in Tables 2 and 3 below.
[0209] “23°:28°” corresponds to the intensity ratio of the strongest X-ray diffraction peak within a 2θ angle of about 23±0.3 degrees to the strongest X-ray diffraction peak within a 2θ angle of about 28±0.3 degrees.
[0210] Table 2
[0211] catalyst Catalyst composition 23°:28° Sample 2 <![CDATA[Ni 3.43 Mg 2.57 Fe 1.50 Rb 0.13 Cr 0.36 Bi 0.60 Ce 1.20 Mo 12 O 48.16 ]]> 1.473 A <![CDATA[Ni 1.81 Mg 1.36 Fe 2.64 Rb 0.13 Cr 0.13 Bi 1.05 Ce 2.11 Mo 12 O 49.18 ]]> 0.548
[0212] Modified XRD Rietveld refinement was performed according to the procedure described above. Peaks related to β-MMoO4 phase (M = Ni, Mg, Fe), Fe2(MoO4)3 phase, m phase and t phase were refined and the ratio of scheelite (m phase + t phase): β-MMoO4 was calculated. The results are reported in Table 3 below.
[0213]
[0214] Based on the elemental composition of the active phase, such as that given in Table 3 for Catalyst Sample 2 and Comparative Example A, a representative percentage of the m-phase can be calculated based on the amount of Ce in the active phase as a percentage of the total active phase. For cases where the stoichiometric amount of Bi in the active phase is greater than the stoichiometric amount of Ce in the active phase, a representative percentage of the m-phase can be calculated assuming that all Ce is in the m-phase and that the m-phase is described by the formula CeBi(MoO4)3. For cases where the stoichiometric amount of Ce in the active phase is greater than the stoichiometric amount of Bi in the active phase, the formula Ce can be used. x Bi (2-x)(MoO4)3 calculates the representative percentage of the m phase, where x is (2n Ce / (n Bi +n Ce )). Based on the known active phase composition, the known atomic weights of the various components, and the appropriate m-phase formula as described above, a representative weight percent of the m-phase can be determined.
[0215] As shown in Table 4, the ratio of measured m-phase to calculated representative m-phase as measured by Rietveld analysis is much lower in the catalyst composition of the present invention (Sample 2) compared to Comparative Example A.
[0216] Table 4
[0217]
[0218] Generally, in some embodiments, the ratio of measured m-phase to calculated representative m-phase as determined by Rietveld analysis is no greater than about 0.1, no greater than about 0.09, no greater than about 0.08, no greater than about 0.07, no greater than about 0.06, no greater than about 0.05, no greater than about 0.04, no greater than about 0.03, or no greater than about 0.02.
[0219] The catalyst composition of the present invention is unique in that it comprises a composite of catalytic oxides of molybdenum, bismuth, cerium, iron, chromium, at least one Group A element, at least one Group B element, and optionally at least one Group C element in specific proportions. This combination of elements in the relative proportions described herein has never been used before in a single ammoxidation catalyst formulation. As shown in Table 1, for the ammoxidation of propylene to acrylonitrile, the catalyst of the present invention exhibits better performance than catalysts containing similar combinations of elements. More specifically, the catalyst of the present invention exhibits a combination of higher total propylene conversion and high selectivity to acrylonitrile compared to similar catalysts.
[0220] When introducing elements of the present invention or preferred embodiments thereof, the articles "a," "an," "the," and "said" are intended to mean that there are one or more of the elements. The terms "comprising," "including," and "having" are intended to be inclusive and mean that there may be additional elements other than the listed elements.
[0221] In view of the above, it will be seen that the several objects of the invention are achieved and other advantageous results attained.
[0222] Although the foregoing description and the above embodiments are typical for the practice of the present invention, it is obvious that many substitutions, modifications and variations will be apparent to those skilled in the art based on this description. Therefore, it is intended that all contents contained in the above description should be interpreted as illustrative rather than restrictive, and all such substitutions, modifications and variations are covered by and fall within the spirit and broad scope of the appended claims.
Claims
1. A catalyst composition comprising a composite of a catalytic oxide, the composite comprising molybdenum, bismuth, cerium, iron, chromium, at least one element of group A, at least one element of group B and optionally at least one element of group C, Group A consists of sodium, potassium, rubidium, and cesium; Group B consists of nickel, cobalt, manganese, zinc, magnesium, calcium, strontium, cadmium and barium; Group C consists of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum and mercury; and The relative ratios of these elements are expressed by formula (1): Mo 12 Bi a Ce b Feb c Cr d A e B f C g O x (1) in: a is about 0.05 to about 4; b is about 0.3 to about 3; c is about 0.01 to about 4; d is from about 0.01 to about 2; e is about 0.01 to about 2; f is about 0.01 to about 10; g is about 0. to about 0.2; x is a value determined by the valence requirements of other elements present; and Wherein c / d is about 2-17.
2. The catalyst composition of claim 1, wherein c / d is from about 7 to about 12, from about 7 to about 11.5, from about 7 to about 11, from about 7 to about 10.5, from about 7.5 to about 10.5, from about 8 to about 10.5, or from about 8 to about 10.
3. The catalyst composition of claim 1, wherein c / d is about 2 to about 16, about 2 to about 14, about 2 to about 12, about 2 to about 10, about 2 to about 8, or about 2 to about 6.
4. The catalyst composition of any one of claims 1-3, wherein the catalyst composition exhibits a scheelite (m-phase + t-phase): β-MMoO4 ratio of not greater than about 0.1, not greater than about 0.09, not greater than about 0.08, not greater than about 0.07, not greater than about 0.06, not greater than about 0.05, not greater than about 0.04, not greater than about 0.03, not greater than about 0.02, or not greater than about 0.01, wherein the amounts of m-phase, t-phase, and β-MMoO4 phases are determined using X-ray diffraction and a modified Rietveld analysis model.
5. A catalyst composition comprising a composite of a catalytic oxide, the composite comprising molybdenum, bismuth, cerium, iron, chromium, at least one element of Group A, at least one element of Group B and optionally at least one element of Group C, Group A consists of sodium, potassium, rubidium, and cesium; Group B consists of nickel, cobalt, manganese, zinc, magnesium, calcium, strontium, cadmium and barium; Group C consists of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum and mercury; and The relative ratios of these elements are expressed by formula (1): Mo 12 Bi a Ce b Feb c Cr d A e B f C g O x (1) in: a is about 0.05 to about 4; b is about 0.01 to about 3; c is about 0.01 to about 4; d is from about 0.01 to about 2; e is about 0.01 to about 2; f is about 0.01 to about 10; g is about 0 to about 0.2; x is a value determined by the valence requirements of other elements present; and wherein c / d is about 2-36 and the catalyst composition exhibits a scheelite (m-phase + t-phase):β-MMoO4 ratio of not greater than about 0.3, wherein the amounts of m-phase, t-phase and β-MMoO4 phases are determined using X-ray diffraction and a modified Rietveld analysis model.
6. The catalyst composition of claim 5, wherein the catalyst composition exhibits a scheelite (m-phase + t-phase): β-MMoO4 ratio of not greater than about 0.25, not greater than about 0.2, not greater than about 0.15, not greater than about 0.1, not greater than about 0.09, not greater than about 0.08, not greater than about 0.07, not greater than about 0.06, not greater than about 0.05, not greater than about 0.04, not greater than about 0.03, not greater than about 0.02, or not greater than about 0.01, wherein the amounts of m-phase, t-phase, and β-MMoO4 phases are determined using X-ray diffraction and a modified Rietveld analysis model.
7. The catalyst composition of claim 5 or claim 6, wherein c / d is about 2 to about 32, about 2 to about 28, about 2 to about 24, about 2 to about 20, about 4 to about 36, about 4 to about 32, about 4 to about 28, about 4 to about 24, about 4 to about 20, about 7 to about 36, about 7 to about 32, about 7 to about 28, about 7 to about 24, about 7 to about 20, about 7 to about 12, about 7 to about 11.5, about 7 to about 11, about 7 to about 10.5, about 7.5 to about 10.5, about 8 to about 10.5, or about 8 to about 10.
8. The catalyst composition of any one of claims 1 to 7, wherein a is about 0.05 to about 3.5, about 0.05 to about 3, about 0.05 to about 2.5, about 0.05 to about 2, about 0.05 to about 1.5, about 0.05 to about 1, about 0.1 to about 1, about 0.15 to about 1, about 0.2 to about 1, about 0.25 to about 1, about 0.3 to about 1, about 0.35 to about 1, about 0.4 to about 1, about 0.05 to about 1.25, about 0.05 to about 0.75, about 0.05 to about 0.5, about 0.05 to about 0.4, about 0.05 to about 0.3, about 0.05 to about 0.2, or about 0.05 to about 0.
1.
9. The catalyst composition of any one of claims 1-4, wherein b is from about 0.3 to about 3, from about 0.4 to about 3, from about 0.5 to about 3, from about 0.75 to about 3, from about 1 to about 3, from about 1.5 to about 3, from about 2 to about 3, from about 2.5 to about 3, from about 0.75 to about 2.5, or from about 1 to about 2.
5.
10. The catalyst composition of any one of claims 5-8, wherein b is about 0.01 to about 2.5, about 0.01 to about 2, about 0.01 to about 1.5, about 0.02 to about 1.5, about 0.04 to about 1.5, about 0.06 to about 1.5, about 0.08 to about 1.5, about 0.1 to about 1.5, about 0.2 to about 1.5, about 0.3 to about 1.5, about 0.4 to about 1.5, about 0.5 to about 1.5, about 0.1 to about 3, about 0.2 to about 3, about 0.3 to about 3, about 0.4 to about 3, about 0.5 to about 3, about 0.75 to about 3, about 1 to about 3, about 1.5 to about 3, about 2 to about 3, about 2.5 to about 3, about 0.75 to about 2.5, or about 1 to about 2.
5.
11. The catalyst composition of any one of claims 1 to 10, wherein c is from about 0.05 to about 4, from about 0.1 to about 4, from about 0.15 to about 4, from about 0.5 to about 4, from about 0.25 to about 4, from about 0.3 to about 4, from about 0.35 to about 4, from about 0.4 to about 4, from about 0.45 to about 4, from about 0.5 to about 4, from about 0.75 to about 4, from about 1 to about 4, from about 1 to about 3.5, from about 1 to about 3, from about 0.01 to about 3.5, from about 0.01 to about 3, from about 0.01 to about 2, from about 0.01 to about 1, from about 0.01 to about 0.5, from about 0.01 to about 0.4, from about 0.01 to about 0.3, from about 0.01 to about 0.2, from about 0.01 to about 0.1, or from about 0.01 to about 0.
05.
12. The catalyst composition of any one of claims 1 to 11, wherein d is from about 0.01 to about 1.5, from about 0.01 to about 1, from about 0.02 to about 1, from about 0.04 to about 1, from about 0.06 to about 1, from about 0.08 to about 1, from about 0.1 to about 1, from about 0.15 to about 1, from about 0.15 to about 0.5, from about 0.02 to about 2, from about 0.05 to about 2, from about 0.1 to about 2, from about 0.5 to about 2, from about 1 to about 2, or from about 1.5 to about 2.
13. The catalyst composition of any one of claims 1-12, wherein e is about 0.01 to about 1.5, about 0.01 to about 1, about 0.01 to about 0.5, about 0.01 to about 0.4, about 0.01 to about 0.3, about 0.01 to about 0.3, about 0.02 to about 0.3, about 0.04 to about 0.3, about 0.06 to about 0.3, about 0.08 to about 0.3, about 0.1 to about 0.5, or about 0.2 to about 0.
4.
14. The catalyst composition of any one of claims 1 to 13, wherein f is about 0.02 to about 10, about 0.04 to about 10, about 0.06 to about 10, about 0.08 to about 10, about 0.1 to about 10, about 0.2 to about 10, about 0.4 to about 10, about 0.6 to about 10, about 0.8 to about 10, about 1 to about 10, about 1.5 to about 10, about 2 to about 10, about 2.5 to about 10, about 3 to about 10, about 3 .5 to about 10, about 4 to about 10, about 4.5 to about 10, about 5 to about 10, about 0.01 to about 8, about 0.01 to about 7, about 0.01 to about 6, about 0.01 to about 5, about 0.01 to about 4, about 0.01 to about 3, about 0.01 to about 2, about 0.01 to about 1, about 0.01 to about 0.5, about 0.01 to about 0.25, about 0.01 to about 0.2, about 0.01 to about 0.1, or about 0.01 to about 0.
05.
15. The catalyst composition of any one of claims 1-14, wherein g is from about 0.01 to about 0.2, from about 0.02 to about 0.2, from about 0.04 to about 0.2, from about 0.06 to about 0.2, from about 0.08 to about 0.2, or from about 0.1 to about 0.
2.
16. The catalyst composition of any one of claims 1-14, wherein g is from about 0 to about 0.15, from about 0 to about 0.1, from about 0 to about 0.05, from about 0 to about 0.04, from about 0 to about 0.03, from about 0 to about 0.02, or from about 0 to about 0.
01.
17. The catalyst composition according to any one of claims 1 to 16, wherein A is selected from potassium, rubidium and cesium.
18. The catalyst composition according to any one of claims 1 to 16, wherein A is selected from rubidium and cesium.
19. The catalyst composition according to any one of claims 1 to 18, further comprising a support.
20. The catalyst composition of claim 19, wherein the carrier comprises about 30 wt.% to about 70 wt.%, about 35 wt.% to about 70 wt.%, about 40 wt.% to about 70 wt.%, about 40 wt.% to about 65 wt.%, about 40 wt.% to about 60 wt.%, about 40 wt.% to about 55 wt.%, or about 45 wt.% to about 55 wt.% of the catalyst composition.
21. A method for the ammoxidation of olefins, the method comprising: Olefins are reacted in the gas phase at elevated temperature and pressure with a gas containing molecular oxygen and ammonia in the presence of a catalyst composition according to any one of claims 1 to 20.
22. The process of claim 21, wherein the olefin is selected from propylene, isobutylene or mixtures thereof to produce a reaction product comprising acrylonitrile, methacrylonitrile and mixtures thereof, respectively.
23. The process of claim 21 or claim 22 wherein the molar ratio of ammonia to olefin is from about 0.5:1 to about 2:1, from about 0.5:1 to about 1.5:1, from about 0.5:1 to about 1.4:1, from about 0.5:1 to about 1.3:1, from about 0.5:1 to about 1.2:1, from about 0.5:1 to about 1.1:1, from about 0.5:1 to about 1:1, or from about 0.75:1 to about 1:
1.
24. The process of any one of claims 21-23, wherein the olefin comprises propylene and the molar ratio of ammonia to propylene is from about 0.9: 1 to about 1.3: 1, from about 0.9: 1 to about 1.2: 1, from about 0.9: 1 to about 1.1 : 1, from about 1 : 1 to about 1.1 : 1, or from about 1 : 1 to about 1.05:
1.
25. The process of any one of claims 21-24, wherein the source of olefins comprises propylene and oxygen comprises air, and wherein the molar ratio of air to propylene is from about 5: 1 to about 20: 1, from about 5: 1 to about 15: 1, from about 6: 1 to about 12: 1, from about 7: 1 to about 15: 1, from about 8: 1 to about 15: 1, from about 8: 1 to about 14: 1, from about 8: 1 to about 13: 1, or from about 8: 1 to about 12:
1.
26. The process of any one of claims 21-25, wherein the olefin comprises propylene and the olefin conversion is about 85% or greater, about 86% or greater, about 87% or greater, about 88% or greater, about 89% or greater, about 90% or greater, about 91% or greater, about 92% or greater, about 93% or greater, about 94% or greater, about 95% or greater, about 96% or greater, about 97% or greater, about 98% or greater, about 99% or greater, about 99.1% or greater, about 99.2% or greater, about 99.3% or greater, about 99.7% or greater, about 99.8% or greater, about 99.6% or greater, about 99.7% or greater, about 99.8% or greater, or about 99.9% or greater.
27. The process of any one of claims 21-26, wherein the olefin comprises propylene and the nitrile yield is about 70% or greater, about 72% or greater, about 74% or greater, about 76% or greater, about 78% or greater, about 80% or greater, about 82% or greater, about 84% or greater, about 86% or greater, about 88% or greater, or about 90% or greater.
